Pelaksanaan Program Pengendalian Demam Berdarah Oleh Pemerintah Kota Tanjungpinang - Alfariq Ramadani; Novi Winarti; Rizky Octa Putri Charin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The implementation of dengue fever control in Tanjungpinang City through the 1 House 1 Jumantik Movement program has not been optimal until now. The problem in controlling dengue fever through this program is that the community is inactive and does not know about the implementation of this program. The purpose of the researcher was to determine the implementation of dengue fever control through the 1 House 1 Jumantik Movement program in Tanjungpinang City. Qualitative Method and Policy Implementation theory by Marilee S Grindle. The results of the study showed (1) Content of policy, the researcher found from the indicators of the resources used, namely financial resources, the wages given were only enough for transportation costs. Insufficient resources also limited the number of jumantik cadres working, plus there was a change in funding sources to BOK which caused several health centers to experience a budget reduction in Jumantik honorariums (2) Context of Implementation found that the authority of each actor was not in accordance with the implementation manual for the 1 House 1 Jumantik Movement by the Ministry of Health. In addition, the government also did not provide guidance to the community so that many people did not know about this program.